Survey of transition skills instruction for youth with emotional and behavioral disorders - Mueting, Amy L. (Kansas State University, 2006)
The current study, based solely on teacher-report, provides descriptive data regarding current transition-related instructional practices among Kansas special educators of secondary-aged youth with emotional and behavioral disorders. Students with E/BD are the least likely of all students with disabilities to gain and maintain positive post-school outcomes in the areas of employment, personal-social skills, and community and independent living. Students who demonstrate functional life skills and self-determination skills independent of instruction and directive generally report a higher quality of life than those who are unable. Transition-related instruction specifically addressing functional life skills and self-determination skills may assist these students in their quest for positive post-school outcomes. Research indicating what, if any, transition skills instruction these students receive is not available. Teachers (N = 165) reported a desire to provide transition skills instruction to youth with E/BD (N = 1,076) yet reported having very little transition training (fewer than eight clock hours) and providing very little instruction (less than two hours weekly). Teachers reported that many students with E/BD do not demonstrate life skills and self-determination skills independent of instruction or directive, yet fewer than 11% of the student population had, within their IEP, a goal addressing the specified transition skills. IDEA 2004 regulations mandate that teachers address the transition needs of students with disabilities within a statement of needed transition services, which is not happening with any regularity. The self-determination skills of demonstrating positive social interactions, making appropriate choices and decisions, and employing self-regulation, though often deficits of youth with E/BD, were among the skills mentioned least frequently within the goals of these students. Based on the Pearson r correlation-coefficient analysis no significant relationship was indicated between the number of years of experience of the teachers and the number of minutes of transition instruction teachers provided to this student population. Very few significant relationships existed between the level of independence students reportedly demonstrate each life skill and self-determination skill and a) the amount of transition training the teacher had received and, b) the amount of transition-related instruction teachers reportedly provide. The teacher’s focus has frequently shifted from transition to educational reform.
Keywords: Self-determination; Life skills; Special education; Emotional disturbance; IDEA 2004; Transition education; Education, Secondary (0533); Education, Special (0529); Education, Teacher Training (0530)